Efficacy of Bacillus Thuringiensis Berliner Against Metisa Plana Walker and its Application using Thermal Fogger and Mistblower - Tan, Sek Yee (2004)
The effectiveness of Bacillus thringiensis Berliner (Bt) against the bagworm, Metzsa plana Walker and its application using thermal fogger and mistblower was studied in threeyear old oil palms. Initially, a standardized rearing protocol of the bagworm was established to produce healthy test insects. Met& plana was reared on oil palm seedlings fiom eggs surfacesterilized for one hour in 8% formaldehyde. This sterilization regime did not affect the egg hatchability and it significantly (P<0.05)in creased the survivorship of the first to second instar larvae when compared to larvae hatched from unsterilized eggs. Following a laboratory bioassay conducted against the third and fifth instar larvae at temperatures of 2529°C and 50-80% relative humudity, formulations from both Bt subsp. kurstaki: ~ i ~ eElS@, D ipel@D F, Dipel@W P and ABG-6429 FC; and Bt subsp. aizawai: FlorbacB SC and ~entar i@W G were shown to be effective on the bagworm. Evaluation on the suitability and effectiveness of portable thermal fogging (PulsFogQK10 and AgroFoga AF 35) and mistblower (solo@ Master 412) application of Bt (Dipel ES@) against M. plana in three-year old oil palm revealed that when water was used as the diluent in spray mixtures, efficacious activity was achieved which was attributed from the formation of an adequately stable emulsion. For both types of applicators, the kill of M. plana was shown to be positively dependent on droplet densities and concentrations of Bt. In the field trial on three-year old oil palm, Agro~og@AF 35 with AFX Fogging Solution and solo@ Master 412 Knapsack Mistblower were shown to give effective horizontal throw of 6 m whereas P ~ ~ S FO~@w-KasI oOn ly 2 m. Under the condition of these experiments, cost effectiveness analysis showed that the use of portable fogger to apply Bt formulation to control M. plana was not as cost-effective, practical or suitable as knapsack mistblower. The predicted kill of the bagworm obtained by mistblower was satisfactory and higher (50-92%) compared to thermal fogger (38-46%) at the middle and top strata of the oil palm. The poor deposition rates from fogging application in the palm increased the usage of ~ i ~ e ElS@ an d AFX Fogging Solution thus incurred higher cost. Furthermore, the fogging application was limited to early morning or late evening, and that also incurred higher labour cost, notwithstanding the possibility of labour shortage. Comparatively, the use of mistblower gave higher deposition rates that reduced the rates of ~ i ~ eElS@ per hectare thus saved cost. Mistblower is also easily available, versatile and can be used during the daytime.